ANALISIS KESEDIAAN MEMBAYAR (WILLINGNESS TO PAY) KONSUMEN TERHADAP SAYURAN ORGANIK DI PASAR MODERN PURWOKERTO DAN FAKTOR-FAKTOR YANG MEMENGARUHI - Fatha Fajria; Dyah Ethika; Djeimy Kusnaman (Universitas Sebelas Maret, 2020)
Organic vegetable tend to have higher price than inorganic vegetable, so that the majority of consumers consider vegetable organic products as an expensive food product. This study aims to describe the characteristics of organic vegetable consumer, to analyze the maximum average of willingness to pay and the factors affected the willingness to pay of organic vegetables. This research applied survey method and conducted in the modern market of Purwokerto in August until September 2019. One hundred respondents were taken by using purposive sampling method. Analysis of the data used is descriptive, Contingent Valuation Method (CVM) and Logistic Regression Analysis. The results showed that the average maximum of WTP for organic vegetable lettuce is higher 9.15%, mustard greens is higher 8.70%, kale is higher 8.35%, spinach is higher 10.50%, and broccoli is higher 10.05% than recent price of it. The factors that significally affected the willingness to pay is education, employment, and income, while age, sex, status of marriage, price, and quality do not have any effects to WTP.